Analisis Penerapan Perencanaan Pajak Melalui Metode Penyusutan Aset Tetap Untuk Efisiensi Pembayaran Pajak di PT. Dapur Sarwo Ono - Dwi Firmansyah; Nurwati Nurwati (Indonesian Journal of Economics Application (IJEA), 2020)
The purpose of this study is firstly to analyze the calculation of depreciation of fixed assets using the straight-line method and declining balances to see tax efficiency. Secondly, to analyze the amount of tax planning. Thirdly, to find out the amount of tax savings by doing tax planning. The observed enterprise as a case studi is PT. Sarwo Ono's kitchen. This research uses a descriptive qualitative method with the survey method. Based on the results of this study, we found that PT. Dapur Sarwo Ono uses the straight-line depreciation method in calculating the depreciation expense of its fixed assets; the user of the method applied is for PT. Sarwo Ono's kitchen. Choosing tax planning using a straight line, the company will save tax of Rp. 128,366,517, and if the company uses the declining balance method, the company will save tax by Rp. 129,676,087.